2017
DOI: 10.1111/jocn.14126
|View full text |Cite
|
Sign up to set email alerts
|

Experiences of encounters with healthcare professionals through the lenses of families living with chronic illness

Abstract: Having a participating family member increased the sense of power in families during encounters with healthcare professionals. This participation constitutes a level of support, making it easier for families to handle everyday life due to illness. Family members are, in most cases, included in discussions and decisions, both before and after encounters, and it should be a natural for healthcare professionals to invite them to the encounter too. This is an offer that may not fit every family, but the person wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(30 citation statements)
references
References 50 publications
(69 reference statements)
1
29
0
Order By: Relevance
“…They take over and make decisions about the older person's needs to increase the feeling of being safe, but the results show that this gives the older person a feeling of being deprived of autonomy. In line with the results of this study, previous studies (Årestedt et al, 2018;Mazer et al, 2014) have found that family members base the conversations with healthcare providers on their own beliefs and consider it as their mission and duty to speak for and to see to the older person's interests. The families explained their actions and stated how illness in older persons was not taken seriously by healthcare providers.…”
Section: Discussionsupporting
confidence: 89%
“…They take over and make decisions about the older person's needs to increase the feeling of being safe, but the results show that this gives the older person a feeling of being deprived of autonomy. In line with the results of this study, previous studies (Årestedt et al, 2018;Mazer et al, 2014) have found that family members base the conversations with healthcare providers on their own beliefs and consider it as their mission and duty to speak for and to see to the older person's interests. The families explained their actions and stated how illness in older persons was not taken seriously by healthcare providers.…”
Section: Discussionsupporting
confidence: 89%
“…Concretely, caregiver’s resilience refers to how caregivers use effective coping strategies, transforming the burden of caregiving into strengths [ 56 ]. Dialogue and communication are presented as a fundamental element for the correct coping of the living, with processes both between couples [ 36 , 50 ] and between the different members of the family [ 7 , 37 , 40 , 43 ]. These was also identified by Helgeson et al (2018), Dekawaty et al [ 33 ], Bertschi et al [ 54 ], Gibbons et al, [ 55 ] and Riffin et al [ 52 ] who describe how dyadic or communal coping may favor adaptation to LTCs [ 33 , 50 , 52 , 54 , 55 ].…”
Section: Resultsmentioning
confidence: 99%
“…As disability becomes an increasingly important component of the disease burden and a larger component of healthcare expenditure, new strategies are needed to improve care for people with LTCs and their family caregivers [ 1 , 4 , 5 , 6 ]. Patients and family members live with one or more LTCs for many years because living with an LTC is not only an individual concern, but also a family affair [ 7 , 8 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…'s study on the experience of family health conversations among families coping with chronic health problems also identified the nurse's curiosity, interest, openness, neutrality and involvement as essential elements of their experience . These attitudes, combined with nurses’ skills, allowed for meaningful encounters in which family members felt they were really working with the nurse to find their own solutions to the challenges they faced and were in a respectful, egalitarian, nonhierarchical relationship . These significant meetings were also made possible because of the characteristics of the interventions at the heart of FSS family conversations.…”
Section: Discussionmentioning
confidence: 99%
“…This article presents the families’ experience of family conversations, obtained through a qualitative study based on semi‐structured interviews. This study was based on the family system nursing (FSN) approach, which involves adopting a paradigm shift towards a focus on the family rather than on individuals and simultaneously considering individuals, the relationships that unite them, and the family system they comprise .…”
Section: Methodsmentioning
confidence: 99%